The Development of Agricultural Land Conversion: Legal Culture and Comparative Law in Indonesia and Nigeria - Suhadi Suhadi; Asmarani Ramli; Tri Andari Dahlan; Uche Nnawulezi; Mary-Ann Onoshioke Ajayi (Universitas Negeri Semarang, 2024)
Land conversion is an important issue in Indonesia and Nigeria, with significant economic, social and environmental impacts. The problem-solving approach to uncovering farmers' legal culture is done through a sociolegal approach, where the law is seen not limited to the text but also its context in reality in society. With the sociolegal approach, the values, attitudes and views (NSP) of farmers towards their agricultural land, towards LP2B policies, and the behaviour of farmers in the use and utilization of their agricultural land designated as sustainable food agricultural land can be revealed and constructed appropriately and adequately. This research aims to uncover how farmers' legal culture can be better integrated in the law enforcement of food agricultural land protection, as well as find ways to harmonize formal laws with local practices in order to achieve more effective and equitable land protection, in addition to comparing factors affecting land conversion in both countries, including urbanization, infrastructure and industrial development, and government policies. The economic impacts of land conversion include economic growth and job creation, but also threaten food security and farmers' livelihoods. Social impacts include land conflicts and changes in people's lifestyles, while environmental impacts include deforestation, erosion and flooding. Proposed solutions include stronger monitoring and law enforcement, community participation, and sustainable policies and empowerment programs for farmers. In conclusion, wise policies and active participation from all parties are needed to sustainably manage land conversion in Indonesia and Nigeria.